Identification and Prevalence of Endoparasite on Layer Chicken in Udanawu Sub-district Blitar - Khalissa Farah Alifia; Setiawan Koesdarto; Yulianna Puspitasari; Mufasirin; Adiana Mutamsari Witaningrum (Universitas Airlangga, 2023)
The aim of this research was to determined the prevalence and infection degrees of endoparasite on layer chicken in Sub-district Udanawu, Blitar. Ninety-six samples were taken from layer chicken in 3 different villages namely Bakung Village, Tunjung Village, and Slemanan Village. The examinations taken in this study are fecal examination using native, sediment, and floating methods and blood examination using blood smear method. Result showed that 81.25% samples are positive for helminthiasis infection consisting of Ascaridia galli (66.67%), Heterakis gallinarum (45.83%), Raillietina sp. (31.25%), and Strongyloides avium (7.29%). Blood examination result shown there is no positive sample that infect layer chicken in Sub-district Udanawu, Blitar. Chi-Square test result showed there are significant difference (P<0.05) of Ascaridia galli and Heterakis gallinarum in Bakung Village, Tunjung Village, and Slemanan Village in Sub-district Udanawu, meanwhile there are no significant difference (P>0.05) of Raillietina sp. and Strongyloides avium. Range of infection degrees of helminthiasis in Bakung village, Tunjung village, and Slemanan Village are 608.75 ± 588.53, 223.12 ± 359.21, 156.25 ± 332.39. There are significant difference (P<0.05) on helminthiasis infection degree of layer chicken in Udanawu District, Blitar.